👤

When the polynomial P(x) = x3 + 3x2 -2Ax + 3, where A is a constant, is divided by x2 + 1 we get a remainder equal to -5x. Find A.

nonsense report


Sagot :

Answer:

Divide x(3 + 3x2 -2Ax + 3) by (x2 + 1) to obtain a remainder = -x(1 + 2A)

-x(1 + 2A) = 5x : remainder given

-(1 + 2A) = 5 : polynomials are equal if they corresponding coefficient area equal.

A = -3

Answer:

A=3

Step-by-step explanation:

x2+1 / x3 + 3x2 - 2Ax + 3

x+3

x2+1 /x3 + 3x2 - 2Ax + 3

-x3 + x

3x2 + x - 2Ax + 3

-3x2 + - 3

0 + x - 2Àx = -5x

x - 2Ax - x = -5x - x

-1/2x(-2Ax) = -6x/-2x

A=3